A Mentee's perspective on Dr. Anthony Monaco: the quiet giant of transplantation - Nadig, Satish N. (Frontiers in Transplantation, 2024)
A mentee's perspective of an academic journey on a path paved by a pioneering transplant surgeon-scientist.